TINGKAT PENGETAHUAN MAHASISWA SEMESTER 4 TENTANG SENAM HAMIL DI AKADEMI KEBIDANAN TAHIRAH AL BAETI BULUKUMBA - Erniawati; Nurul Hidayah Bohari; Serli Ekawati; Haerani (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2020)
Pregnancy exercise is physical exercise consists of certain movements that are done specifically to improve the health of pregnant women. Pregnant exercise is recommended to be done by pregnant women in order to facilitate labor.Students of the Tahirah Al BaetiMidwifery Academy in Bulukumba (AKTABE) are midwives candidates whose competence will be in direct usefulto pregnant women in the community. One of the competencies that a prospective midwife must have is to assist pregnant women in the delivery process, so that knowledge of pregnancy exercise is main keyimportant to be understood by students of the AKTABE.. This study aims to determine the level of knowledge of the fourth semester students of AKTABE about pregnancy exercise. This research used descriptive method by using a test sheet as a research instrument. The sampling technique was total sampling, with a total sample of 32 respondents.. The results showed that the levelof knowledge of respondents about pregnancy exercise and the goals of pregnancy exercise were in the poor category (53.1% and 59.4%), followed by moderate knowledge (37.5% and 40.6%) and the good category ( 9.4% and 0). While the knowledge about the meaning, role and benefits of pregnancy exercise were in the moderate category (53.1%; 62.5% and 59.4%), less (3.1%; 34.4% and 28.1%) and good. (9.4%; 3.1% and 12.5%) respectively. Generally, the fourth semester students of AKTABE were still in the sufficient category. This is probably due to the course material of pregnancy exercise in AKTABE is still part of the antenatal care course so that students do not learn pregnancy exercise efectively. The level of knowledge of the fourth semester students of AKTABEabout pregnancy exerciseis generally in the sufficient category.